The The Influence of Ciacianese Buton Dialect (CBD) Towards Students’ English Pronunciation - Tawary, Dhiayuddin Dzulfikar W; Linggar Bharati, Dwi Anggani; Rozi, Fahrur (Universitas Negeri Semarang, 2020)
This study was intended to reveal the information on the influence of the Ciacianese Buton Dialect (CBD) towards the students’ pronunciation of English vowels, diphthongs, consonants, and consonant clusters. The study also explained the effort of the teacher in improving the students’ pronunciation. The subjects of this study were eleventh-grade students at SMAN 2 Pasarwajo, Buton regency. This study employed a descriptive qualitative study toward 30 students of grade XI at SMAN 2 Pasarwajo. This study uses several methods in obtaining the data. They are questionnaires, students’ recordings, interviews, and observation. The results of the study describe that the Ciacianese dialect influences the students’ pronunciation of English sounds positively and negatively. Ciacianese dialect gives positive transfer to sounds /e/, /ʊ/, /ɔ/, /ɔ:/, and /ɪ of vowels; sounds /oʊ/, /ɔɪ/, aʊ/, /ɪə/, /ɛə/, /aɪ/, and /eɪ/ of diphthongs; sounds /b/, /d/, /f/, /g/, /h/, /k/, /l/, /m/, /n/, /p/, /ŋ/, /r/, /ʤ/, /s/, /t/, /w/, /j/ and /z/ of consonants; and sounds /nd/, /mp/, /tr/ and /str/ of consonant clusters. Furthermore, Ciacianese dialect gives negative transfer to sounds /i:/, /ɑ:/, /u:/ æ/, /ʌ/ /ə/ and /æ/ of English vowels; sound /ʊə/ of diphthong; and sounds /ʒ/, /v/, /ð/, /θ/, /ʧ/, and /ʃ/ of English consonants. Lastly, since most of the mispronunciation is caused by the lack of pronunciation practice, the teacher should consider providing more spaces for the students to practice the pronunciation. Keywords: Ciacianese Buton Dialect, Language Acquisition, Students’ Pronunciation.